De fantasmes, bruixes i masies encantades. Terror rural i monstruós femení en Irene Solà i Layla Martínez - de Benito Mesa, Iris (Studia Romanica Posnaniensia, 2025)
This work discusses the novels I gave you eyes and you looked towards darkness by Irene Solà and Woodworm by Layla Martínez in order to reveal the directions taken by feminist narratives of the uncanny in the Iberian context. We address several concepts, such as the Feminist Rereading of the Witch Hunts or the Witchcraft Narratives. The latter allows to trace the founding attributes of the modern witch prototype, which associates women with the abject, scatological, diabolical, and immodest, especially in relation to their sexuality. While establishing continuity with previous works studying the representations of the haunted house, in Solà’s and Martínez’s novels the house is a highly complex locus, housing ghosts, spirits, old witches, and aberrant events. Since our analysis is concerned with feminist uses of the uncanny and monstrosity, it leads to rethink home as a space for women’s confinement. Finally, certain elements of the so-called folk horror contribute to delineate the ways in which the rural landscape becomes a significant element of this Iberian uncanny. We explore as well how the rural setting and natural surroundings engage in a precise dialogue with the archetype of the old witch, potentially embodied by various characters in both novels.